Improving marine protected area with coordination platform: Mud shrimp conservation in Taiwan case study. (September 2021) - Hung, Yi-Ping; Chang, Yi; Truong, Minh-Phuong N.; Yang, Jen-Han; Hsu, Tung-Yao; Hsiao, Shih-Chun
Abstract: Marine protected areas (MPAs) exist worldwide to alleviate the gap between human development and conserving nature, history/culture heritage, and resources. In Taiwan, most of MPAs were established as aquatic organism and fishery resource conservation zones (FCZs), such as mud shrimp ( Austinogebia edulis ) protection since 2006, which we used as a study case. However, comprehensive review has yet conducted to determine whether management objectives are being achieved. We therefore examined the FCZs management effectiveness by conducting a 4 year (2017–2020) field survey of mud shrimp density in the tidal flat and MPA institution in Taiwan. The mud shrimp density obtained from both historical record in references and our observations was analyzed using geographic information systems to determine their spatial distribution within and around the designated FCZs. The results indicate that mud shrimp density is dominant outside the protected zones, which might be related to habitat changes over time. Moreover, the review of MPA governance in Taiwan indicated that FCZs management lack regular financial support and regular examination of management plan. An operational framework is suggested to improve the sustainable management of conservation zones decision-making that comprises four steps: (1) Partnerships with MPA commitment authorities and non-government organizations, specifically, regional fisheries associations; (2) plan regular financial support and fundraise; (3) conduct long-term monitoring programs; and (4) create a coordination platform with stakeholders to evaluate the management plan and/or induce necessary adjustments. This framework will enable users to create strategies that strengthen long-term monitoring and MPA operation maintaining socioeconomic linkages with stakeholders.